2014
DOI: 10.1097/hjh.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of the fetal genotype on maternal blood pressure during pregnancy

Abstract: The heritability of pregnancy-induced hypertension (encompassing both gestational hypertension and preeclampsia) is around 0.47, suggesting that there is a genetic component to its development. However, the maternal genetic risk variants discovered so far only account for a small proportion of the heritability. Other genetic variants that may affect maternal blood pressure in pregnancy arise from the fetal genome, for example wild-type pregnant mice carrying offspring with Cdkn1c or Stox1 disrupted develop hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 104 publications
1
14
0
Order By: Relevance
“…This adds to previous reports of genetic associations found between autosomal fetal but not maternal variants and gestational hypertension in small, unreplicated studies 22,23 and variable associations between maternal blood pressure and interactions between fetal sex and maternal variants 2426 . Our results are consistent with the suggestion that the fetal genome is able to influence maternal blood pressure in pregnancy 7,8 , although they are associations rather than demonstrating causality. When the alleles from these variants were amalgamated as a composite score there were significant associations demonstrated with each of three maternal blood pressure readings taken across the second half of pregnancy in our Cambridge cohorts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This adds to previous reports of genetic associations found between autosomal fetal but not maternal variants and gestational hypertension in small, unreplicated studies 22,23 and variable associations between maternal blood pressure and interactions between fetal sex and maternal variants 2426 . Our results are consistent with the suggestion that the fetal genome is able to influence maternal blood pressure in pregnancy 7,8 , although they are associations rather than demonstrating causality. When the alleles from these variants were amalgamated as a composite score there were significant associations demonstrated with each of three maternal blood pressure readings taken across the second half of pregnancy in our Cambridge cohorts.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that fetal genes may influence maternal metabolism and physiology 6 and we hypothesised that fetal growth genes in particular, may influence a mother’s risk of developing gestational hypertension and gestational diabetes 7,8 . Consistent with this, in the Swedish Birth and Multi-Generation Registries 20% of the variability in the risk for preeclampsia could be attributed to fetal genetic effects 9 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Preeclampsia may recur across generations, and the fetal genotype (both maternal and paternal factors) contributes to the risk. 4,5 It is hypothesized that the pathophysiological events proceed in 2 phases. In early pregnancy, the placental function is probably disturbed by abnormal maternal immune responses to the trophoblast.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous evidence that fetal genotypes may affect processes that alter pre- and postnatal maternal physiology (Liu et al 2015a; Petry et al 2007, 2014), we hypothesized that the circulating levels of maternal organohalogens could also be influenced by fetal genetic factors that might play an active role in controlling the toxicant disposition between mother and fetus. Surprisingly, we found that the heritability and genetic correlation results for midgestational levels of BB-153, BDE-47, -99, -100, -153, and Sum PBDE showed evidence for a higher impact of the total fetal genome-wide SNP-based genetic effects on maternal compound levels than the total maternal genetic effects, using equivalent datasets.…”
Section: Discussionmentioning
confidence: 99%